Everything, everywhere, almost at once - Jacob Kæstel-Hansen; Nikos S Hatzakis (eLife, 2024)
A new platform that can follow the movement of individual proteins inside millions of cells in a single day will help contribute to existing knowledge of cell biology and identify new therapeutics.